Music and the mind - Storr, Anthony (London Harper Collins Publishers, 1992)
Drawing on his own life long passion for music and synthesizing the theories of Plato, Schopenhauer, Stravinsky, Nietzsche, Bartók, and others, distinguished author and psychologist Anthony Storr illuminates music's deep beauty and timeless truth and why and how music is one of the fundamental activities of mankind. A look at music and its relation to human perception traces the origins of music and its functional development in human society as entertainment, communication, and therapy, arguing for the universality and centrality of music.